Dibenzofuran: a model compound for dioxins and furans biodegradation - Nordin, Noor Faizul Hadry; Abdullah Sani, Muhamad Shirwan; Ahmad, Farah Najwa; Sanusi, Najwa Husna; Mat Shaari, Nurul Elyni (Independently published, 2023)
Dibenzofuran: A Model Compound for Dioxins and Furans Biodegradation" provides a comprehensive and in-depth analysis of the various aspects of dioxin and furan pollution and their biodegradation using dibenzofuran as a model compound. It combines scientific research, case studies, and innovative approaches, making it an essential resource for researchers, scientists, environmental professionals, and policymakers working in the field of environmental remediation and pollution control.